Ceruloplasmin Interferes with the Assessment of Blood Lipid Hydroperoxide Content in Small Ruminants - Stefano Cecchini Gualandi; Raffaele Boni (MDPI AG, 2023)
Simple and inexpensive analytical methods for assessing redox balance in biological matrixes are widely used in animal and human diagnostics. Two of them, reactive oxygen metabolites (ROMs) and total oxidant status (TOS), evaluate the lipid hydroperoxide (LOOH) content of the sample and are based on iron-mediated mechanisms. However, these tests provide uncorrelated results. In this study, we compared these two tests in the blood serum of goat kids and lambs, together with an evaluation of ceruloplasmin (CP) oxidase activity. No significant correlation was found between ROMs and TOS, or between TOS and CP oxidase activity, in either species. Conversely, ROMs and CP oxidase activity were highly correlated in both kid and lamb samples (p < 0.001). A significant progressive reduction in the analytical signal in the ROMs assay was observed when sodium azide, an effective CP inhibitor, was added to the samples before the assay (p < 0.001). This decrease was related to sodium azide concentration (p < 0.01) and was not found when sodium azide was added at the same concentrations in the TOS assay. These findings suggest that ROMs, unlike TOS, may be affected by CP, which interferes with LOOH detection in blood samples.